2010
DOI: 10.1038/hr.2010.113
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomic profiling of uremic solutes in CKD patients

Abstract: Early detection and accurate monitoring of patients with chronic kidney disease (CKD) is likely to improve care and decrease the risk of cardiovascular and cerebrovascular diseases. As a new diagnostic tool, we examined the retention of uremic solutes as a simpler, more accurate method to assess renal function. To achieve this, we comprehensively evaluated these solutes in CKD patients. By capillary electrophoresis with mass spectrometry, we found 22 cations and 30 anions that accumulated significantly as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 30 publications
(35 reference statements)
8
136
1
1
Order By: Relevance
“…It also was confirmed by CE-MS analysis of 41 CKD patients that not only ADMA and GSA, but also transaconitate, exists in human beings and that their concentrations are increased in accordance with CKD progression. 50 ADMA and the other guanidino compounds are discussed in more detail by Schepers et al in this issue. 56 Recently, Toyohara et al showed the pathophysiological function and transcriptional regulation of human SLCO4C1 and introduced novel transporterbased therapeutic strategies for CKD by up-regulating SLCO4C1 expression in the kidney.…”
Section: Role Of Oatp4c1 In Uremic Toxin Clearancementioning
confidence: 99%
See 3 more Smart Citations
“…It also was confirmed by CE-MS analysis of 41 CKD patients that not only ADMA and GSA, but also transaconitate, exists in human beings and that their concentrations are increased in accordance with CKD progression. 50 ADMA and the other guanidino compounds are discussed in more detail by Schepers et al in this issue. 56 Recently, Toyohara et al showed the pathophysiological function and transcriptional regulation of human SLCO4C1 and introduced novel transporterbased therapeutic strategies for CKD by up-regulating SLCO4C1 expression in the kidney.…”
Section: Role Of Oatp4c1 In Uremic Toxin Clearancementioning
confidence: 99%
“…In vitro studies using cloned transporters have greatly expanded our knowledge concerning the interaction of identified uremic toxins with OATs (Tables 1 and 2 50 ) values. Seven of these uremic solutes, p-hydroxyhippuric acid, 3-carboxy-4-methyl-5-propyl-2-furanopropanoic acid (CMPF), hippuric acid, indoleacetic acid, indoxyl sulfate, uric acid, and xanthine, have reported both increased in vivo plasma levels in uremic patients and in vitro kinetic parameters showing interaction with OATs.…”
Section: Potential Of Uremic Toxins To Cause Clinically Relevant Intementioning
confidence: 99%
See 2 more Smart Citations
“…Over 100 molecules have been implicated in the pathogenesis of uremic syndrome (57)(58)(59)(60). Their precise roles are debated, but many of these are small organic anions, such as indoxyl sulfate, carboxy-methyl-propyl-furanpropionate, p-cresol sulfate, and kynurenine; molecules associated with CKD that can accumulate between dialysis sessions (57,59).…”
Section: Uremic Toxinsmentioning
confidence: 99%